Engagement + Expertise = Trust? Comparing Pathways to Credibility for Journalism and Healthcare - Young Eun Moon; Sung-Hee Wendy Paik; Kristy Roschke; Jacob L. Nelson; Seth C. Lewis (Journalism and Media, 2025)
Many journalists believe they must become more engaged with the public to improve trust in news. What remains unknown is how the public weighs the trustworthiness of engagement relative to the trustworthiness of a more traditional journalistic value: expertise. This study aims to address this gap by assessing public perceptions of engagement and expertise within journalism and comparing them with perceptions of expertise and engagement within another institution dealing with similarly high levels of distrust: healthcare. Professionals within both journalism and healthcare are attempting to mitigate their trust crises by increasing their engagement with the people they seek to serve, which means each profession is currently navigating an uncertain balancing act between engagement and people’s perceived expertise that this study seeks to explore. Using a US-based survey (N = 981) and employing structural equation modeling (SEM), we find that, when it comes to journalism, engagement does not significantly influence trust, while perceived expertise has a positive impact. In contrast, perceptions of healthcare specialists show both perceived expertise and engagement positively influencing trust, with engagement having a stronger effect. We conclude by exploring the implications of these findings for the relationship between journalists and the public.